PERAN HUMAS SEBAGAI FUNGSI DOKUMENTASI DAN PUBLIKASI BERITA DI MIN 3 GUNUNGKIDUL - Sri Hartati; Khoirul Anwar (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2023)
To improve MIN 3 Gunungkidul to become a quality school, one way is through public relations management (PR). Public Relations at MIN 3 Gunungkidul plays a role in delivering various information to the public through social media or in person. In this study, the authors reveal how public relations management is carried out at MIN 3 Gunungkidul to improve the quality of madrasas through news publications and find out the factors that support and hinder public relations. The author uses a qualitative research method, with the case study method. In collecting data, researchers used direct observation techniques (observation), interviews, and documentation. The results of this study indicate that in public relations management at MIN 3 Gunungkidul, a team was formed by the Head of the Madrasah who was in charge of publishing news and documenting activities. Factors that support public relations management are the availability of human resources who have high work motivation, teachers who are competent in writing and publishing news, available websites for writing, and the availability of social media to deliver information to student guardians. The inhibiting factors are the location of the madrasah which is less strategic and there are no supporting tools for documenting madrasah programs so that the public relations program runs less than optimally.